The Potential of Red Roses Extract (Rosa Damascena Mill) As an Antiseptic Stomatitis in Snakes (Python Reticulatus) on The Total Number Leukocyte and Defferential Counting of Leukocytes - Dian Ayu Kartika Sari; Novi Setyaningrum (VITEK : Bidang Kedokteran Hewan, 2015)
This study aimed to determine the effect of red roses extracts (Rosa damascena Mill) as an antiseptic stomatitis in snakes (Python reticulatus) on the total number leukocyte and defferential counting of leukocytes. Male snakes with an average weights 200 grams, length of ± 1 to 1.3 m, and derived from same parent, were used as experimental animals in the study. Statistical analysis method using ANOVA with five treatments and four repetitions were continued using HSD test if there were significant differences found in the study. The unhomogenous data processed by ANOVA were continuously processed using Kruskal Wallis test. The treatment groups consisted of the P0 (control +), the P1 (stomatitis control), the P2, P3, P4 (stomatitis treatment). P0 and P1 groups were given placebo the P2, P3, P4 each got a red rose flower extract 12,5%, 25%, 50%. Respectively medications were given topically, once a day, for two weeks. Blood sampling was performed after treatment, respectively counting number and type of leukocytes. Data were analyzed by ANOVA and Kruskal Wallis. Result showed there were no significant differences in leukocytes and all type of leukocytes cells, namely: heterophile, eosinophils, basophils, lymphocytes, and monocytes.